Analysis and comparison of single-phase induction motor operation from single- and two-phase power sources using MATLAB simulation results - Mohamed Adel Esmaeel; Nashaat M. Hussain Hassan (Institute of Advanced Engineering and Science, 2022)
Single phase induction motor (SPIM) has zero torque, this motor has many types and the main objective is to find the starting torque of the motor. This is done by providing auxiliary coils that are mechanically separated or weakened after 75% of the engine speed. The real problem here is that these auxiliary windings occupy a third of the iron core of the motor, and when they are separated or weakened, the capacity of the iron core is not fully used and the main windings must withstand the rated load current alone which shortens the life of the motor and reduces the hours of continuous operation of the motor. In this paper, a single-phase motor is fed from a single-phase power source and again from a two-phase power source, so that the auxiliary coils are not separated after 75% of the motor's speed and have a continuous role in the motor's operation. The torque and current flow in the motor are compared in both cases. Due to the rarity of the two-phase power supply in nominal uses, it can be supplied by a full bridge inverter. This comparison was provided by steady-state analysis and the results of MATLAB Simulink.